Impact of standardized patients on the training of medical students to manage emergencies. Issue 5 (February 2017) - Herbstreit, Frank; Merse, Stefanie; Schnell, Rainer; Noack, Marcel; Dirkmann, Daniel; Besuch, Anna; Peters, Jürgen
Abstract: Background: Teaching emergency management should educate medical students not only for facts and treatment algorithms but also for time effective physical examination, technical skills, and team interaction. We tested the hypothesis, that using standardized emergency patients would be more effective in transmitting knowledge and skills compared with a more traditional teaching approach. Methods: Medical students (n = 242) in their fourth (second clinical) year were randomized to receive either training on standardized patients simulating 3 emergency settings ("acute chest pain, " "stroke, " and "acute dyspnea/asthma") or traditional small group seminars. Before and after the respective training pathways, the students' knowledge base (multiple-choice examination) and practical performance (objective structured clinical examination using 3 different emergency scenarios) were assessed. Results: Teaching using standardized patients resulted in a significant albeit small improvement in objective structured clinical examination scores (61.2 ± 3 for the standardized patient trained group vs 60.3 ± 3.5 for the traditional seminar group; P  = 0.017, maximum achievable score: 66), but no difference in the written examination scores (27.4 ± 2.4 vs 27.0 ± 4.4; P  = 0.341; maximum achievable score: 30). Conclusion: Teaching management of emergencies using standardized patients can improve medical students' performance in clinical tests, and a change from traditional seminars in favor of practice sessions with standardized patients does not compromise the learning of medical facts.